The Berlin Wall : how it rose and why it fell - Epler, Doris M. (Brookfield, Conn. : Millbrook Press, 1992)
A history of the much hated wall that for nearly thirty years divided Berlin and created two separate countries.
Includes bibliographical references (p. 122-125) and index.
School Library Journal.
Voice of Youth Advocates (V.O.Y.A.).
Wilson's Junior High School.
Young Adult
Keywords: Berlin Wall, Berlin, Germany, 1961-1989 -- Juvenile literature; Berlin Wall, Berlin, Germany, 1961-1989.; Berlin Wall, Berlin, Germany, 1961-1989.; Berlin (Germany) -- History -- 1945-1990 -- Juvenile literature; Germany -- History -- 1945-1990 -- Juvenile literature